Increased Petrous Bone Uptake on 18F-PSMA-1007 PET/CT Due to Otospongiosis. (5th May 2023) - Neveü, Sophie; Becker, Minerva; Guinand, Nils; Mainta, Ismini Charis; Lenoir, Vincent
Abstract: We report the case of a 74-year-old man who had undergone radical prostatectomy for prostatic cancer 6 months earlier. Elevated prostate-specific antigen during follow-up prompted 18 F–prostate-specific membrane antigen (PSMA) ligand PET/CT ( 18 F-PSMA-1007 PET/CT) to search for new manifestations of prostate cancer, revealing an increased focal uptake (SUVmax, 5.9) in the left cochlear/pericochlear temporal bone and equivocal PSMA-RADS-3a external iliac nodes. Comparison with cone-beam CT and MRI showed that the focal temporal bone uptake corresponded to the typical morphological features of active otospongiosis (otosclerosis) in the context of a previously known long-standing otospongiosis.